Arteries of the brain in the dog - Hasan Erden; Nejdet Dursun; İsmail Türkmenoğlu (Eurasian Journal of Veterinary Sciences)
The dog has been a frequent subject for laboratory studies ot the cerebral circulation. By means ot co-toroud latex injected preparations, the anatomy of the arterial supply to the brain has been determined in Anatolian shepherd dog. As a material, fourteen adult dogs were used. The main source of blood supply to the brain of the dog is from the internal carotid artery and the basilar artery. The external carotid artery can contribute to perfusion of the brain in dogs through anastomoses between extracranial and intracranial circulations.